APLIKASI PEMBUATAN KOMPOSTER SEDERHANA DI KELURAHAN TELUK KABUNG TENGAH KOTA PADANG DAN KELURAHAN RENGAS CONDONG KABUPATEN BATANG HARI JAMBI - Fitri Yuranda; Amalia Viviani; Zulkarnaini Zulkarnaini (Jurnal Hilirisasi IPTEKS, 2022)
Garbage is something useless that arises as a result of human activities. The waste problem is a difficult thing to solve, due to the increasing population, the volume of household organic waste will also increase in urban areas, which is not accompanied by management, management systems, and public awareness of waste management. One of the appropriate technologies that can overcome waste problems is processing household organic waste using the composting method using a composter based on community empowerment and development programs. The community empowerment and development program for the application of simple composter production was carried out in two locations, namely Teluk Kabung Tengah Village, Bungus Teluk Kabung District, Padang City, West Sumatra Province and RT 032 RW 005 Rengas Condong Village, Muara Bulian District, Batang Hari Regency, Jambi. This community empowerment and development program aims to empower the community and develop community knowledge about processing household organic waste using the composting method using a simple composter. From this activity the community has gained increased knowledge from the community empowerment and skills development program in processing household organic waste into compost using the composting method using a composter as well as motivating the surrounding community in an effort to reduce organic waste in the environment around the activity site. Utilization of organic waste into compost can reduce environmental pollution, has economic value, sells value, and can provide nutrients to plants.